New lead compounds in the search for pure antiglucocorticoids and the dissociation of antiglucocorticoid effects - Pecci, Adali (2009)
Antiglucocorticoids that act as antagonists at the glucocorticoid receptor (GR) level may be used to block or modulate the undesirable effects of glucocorticoid excess (from endogenous or exogenous origin). RU486 developed in the early 80s, is an antiglucocorticoid but also a potent antiprogestin and abortifacient, nevertheless it still remains as the only GR antagonist drug in the market. Further on, in view of the variety of physiological processes in which glucocorticoids are involved, selective antiglucocorticoids that can block only some of these processes (eventually with tissue specificity) would be highly desirable. The bridged pregnane 21-hydroxy-6,19-epoxyprogesterone, was developed as an alternative lead being an antagonist of the GR with no affinity for mineralocorticoid and progesterone receptors. Antagonistic activity was evidenced by partial blocking of dexamethasone induction of tyrosine aminotransferase (TAT) and thymocyte apoptosis. Replacement of the oxygen bridge by a sulfur bridge gave a less bent, more flexible molecule. 21-Hydroxy-6,19-epithioprogesterone exhibited improved antiapoptotic activity on thymocytes but was not effective blocking TAT induction. This selectivity was improved further by oxidation to the sulfone. The sulfone but not the reduced compound also reverted the dexamethasone-mediated inhibition of NFκB activity in HeLa cells. Blocking of the apoptotic effect of TNFα by dexamethasone in the L929 cell line (mouse fibroblasts), was only reverted partially by the sulfone which exhibited a mild agonistic/antagonistic activity in this assay. None of these compounds showed antiprogestin activity. Similar overall molecular shapes but more lipophylic and with higher metabolic stability were obtained by introduction of a methylene bridge (6,19-methanoprogesterone) or by a direct bond between C-6 and C-19 (6,19-cycloprogesterone and its 21-hydroxy derivative). The latter highly bent steroids showed affinity for the GR. Recently we performed molecular dynamics simulations of GR-ligand complexes to investigate the molecular basis of the passive antagonism exhibited by 21-hydroxy-6,19-epoxyprogesterone. On the basis of our findings, we proposed that the passive antagonist mode of action of this antiglucocorticoid analog resides, at least in part, in the incapacity of GR-21-hydroxy-6,19-epoxyprogesterone complex to dimerize, making the complex unable to activate gene transcription. © 2009 Elsevier Ltd. All rights reserved.